A DISCUSSION ON THE RELATION OF FEAR AND POWER IN THE ANCIENT MESOPOTAMIAN SOCIETIES - Sevgi DÖNMEZ (Fırat University, 2019)
In the ancient Mesopotamian belief system, the definition of the evil and scary was always considered in relation with a